Successful in vitro maturation for urgent fertility preservation despite hormonal contraception by continuous progestin application - Rösner, Sabine; Hecht, Stephanie; Germeyer, Ariane; Strowitzki, Thomas (Gynecological endocrinology, 2019)
We report a unique case of a rare utilization of IVM. This case shows the successful retrieval of immature oocytes followed by in vitro maturation (IVM) for fertility preservation in a patient undergoing chronic progestin contraception. A 24-year-old patient with anaplastic astrocytoma requiring chemotherapy with temozolomide for 12 cycles as soon as possible with wish for fertility preservation while using a long acting etonogestrel birth control implant presented in our unit for fertility preservation in May 2017. The currently used implant should be preserved for further contraception. As the ovaries presented with a high, pco-like, antral follicle count, IVM was offered; the patient agreed. A transvaginal follicular puncture in general anesthesia without any hormonal intervention and IVM of gained oocytes was performed. As the patient actually had no spouse, she decided to freeze unfertilized metaphase II stage oocytes (MII). Thirteen oocytes were obtained, eight of them could be matured and cryopreserved. IVM could be a possibility for fertility preservation in patients with polycystic ovaries when no time is available for stimulation for conventional in vitro fertilization. Even use of continuous progestin application for contraception is no obstacle.